Consumer Preference Analysis in Decision-Making to Use Beauty Clinic Services (A Case Study on WPL Aesthetic Clinic Customers in Medan) - Syahfitri, Khofifah Dwi; Wibowo, Rulianda Purnomo; Rini, Endang Sulystia (PT FORMOSA CENDEKIA GLOBAL, 2025)
The aim of this study is to obtain empirical evidence about the ideal profile of consumer preferences and determine the importance and utility values of the attributes that shape consumer preferences in making decisions to use beauty services at WPL Aesthetic Clinic. This study uses conjoint analysis to formulate consumer preferences, assisted by SPSS software. The attributes of consumer preferences in this study include service quality, promotions, and price. The population for this study consists of customers of WPL Aesthetic Clinic, located at Jl. Beo No. 43, Sei Sikambing B, Medan Sunggal District, Medan City. The sample size for this study is 90 patients. Based on the research findings, the importance value for the service quality attribute is 38.79%, making service quality the most important attribute that significantly influences consumer preferences. The significance values for the Pearson's R and Kendall's Tau tests were below 0.05, indicating that the factors or attributes used in this study—service quality, promotions, and price—have a significant impact on influencing consumer preferences in choosing WPL Aesthetic Clinic's services.